Citizen Perception of Local Government Website in Belitung Timur (KOMUNITAS: International Journal of Indonesian Society and Culture, 2022)
This study seeks to see and analyze how the public's perception of the government website of the East Belitung Regency is. This study uses primary data sources in the form of questionnaires distributed to 80 respondents who are people of Belitung Timur who actively use the internet. The data source is then processed using the SmartPLS device to generate data in the form of tables and images to see the reliability, validity and P values. then these results will be tested with 4 related variables, namely data quality, service quality, behavioral, and trust. The results showed that the 4 variables directly affect public perception so that the better the value of the variable, the more positive the public perception. The shortcoming of this research is the number of respondents who are only 80 so that in future research it can be added to the diversity of data results.